A Vörös Őrség - Takács, Gyula (Közép-Európai Közlemények, 2012)
This article focuses on the organization of the Red Guard of the Hungarian Soviet Republic in 1919. Basically it summarizes the main provisions of the ordinance which created the frame of the organization. It tries to outline the principles of the setting-up, the specificity of the judicial proceedings in connection the revolutionary tribunals and the functioning of the regional departments. It briefly reviews the cooperation with the Hungarian Red Army. It also gives some information about the connection between the Red Guards and the atrocities of the ‘red terror’. It mentions the role of the Red Guard in border patrol activities and the criminal investigation activities. This article is only a brief overview of the issue based on some official documents. It is an edited variant of a conference lecture.